Managing of the production performance - Jokić, Zoran; Jevtić, Jelena (Journal of Engineering & Processing Management, 2017)
Today, most companies face numerous problems that are the result of events in a modern business environment. Failure in business can lead to disappointment with both managers and other employees. This paper presents a conceptual framework for enterprise resource management. From the prerequisites of production through the engagement of production factors to the minimization of costs, this paper aims is to illustrate how and with which contribution the production performance is properly managed.